Breathing as a Fundamental Rhythm of Brain Function - Heck, Detlef H.; McAfee, Samuel S.; Liu, Yu; Babajani-Feremi, Abbas; Rezaie, Roozbeh; Freeman, Walter J.; Wheless, James W.; Papanicolaou, Andrew C.; Ruszinkó, Miklós; Sokolov, Yury; Kozma, Robert (Frontiers in Neural Circuits, 2017)
Ongoing fluctuations of neuronal activity have long been considered intrinsic noise that introduces unavoidable and unwanted variability into neuronal processing, which the brain eliminates by averaging across population activity (Georgopoulos et al., 1986;Lee et al., 1988;Shadlen and Newsome, 1994;Maynard et al., 1999). It is now understood, that the seemingly random fluctuations of cortical activity form highly structured patterns, including oscillations at various frequencies, that modulate evoked neuronal responses (Arieli et al., 1996;Poulet and Petersen, 2008;He, 2013) and affect sensory perception (Linkenkaer-Hansen et al., 2004;Boly et al., 2007;Sadaghiani et al., 2009;Vinnik et al., 2012;Palva et al., 2013). Ongoing cortical activity is driven by proprioceptive and interoceptive inputs. In addition, it is partially intrinsically generated in which case it may be related to mental processes (Fox and Raichle, 2007;Deco et al., 2011). Here we argue that respiration, via multiple sensory pathways, contributes a rhythmic component to ongoing cortical activity. We suggest that this rhythmic activity modulates the temporal organization of cortical neurodynamics, thereby linking higher cortical functions to the process of breathing.